Electronic device and manufacturing method thereof, and coating liquid for forming semiconductor layer and manufacturing method thereof

JP7644904B2Active Publication Date: 2025-03-13MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024035776
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2025-03-13
Estimated Expiration
2037-11-08

AI Technical Summary

Benefits of technology

【0008】 半導体層を備える電子デバイスの耐久性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644904000006
    Figure 0007644904000006
  • Figure 0007644904000007
    Figure 0007644904000007
  • Figure 0007644904000008
    Figure 0007644904000008
Patent Text Reader

Abstract

To improve the durability of an electronic device.SOLUTION: A coating liquid including an organic semiconductor compound and a dopant for an organic semiconductor compound which is a hypervalent iodine compound is heated to 85°C or higher and / or the coating liquid is irradiated with ultraviolet light, and then the coating liquid is applied so as to form a semiconductor layer.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electronic device and a method for producing the same, and a coating liquid for forming a semiconductor layer and a method for producing the same. [Background technology]

[0002] The performance of a semiconductor device having a semiconductor layer is greatly affected by the characteristics of the semiconductor layer. For this reason, in research to manufacture high-performance semiconductor devices, improvement of the semiconductor layer is a major target. For example, Non-Patent Document 1 describes that device reproducibility can be improved by producing a perovskite semiconductor layer obtained from methylamine iodide and tin iodide by the LT-VASP method. In addition, Non-Patent Document 1 uses poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) doped with 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB) as the material for the hole transport layer. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] T. Yokoyama et al. "Overcoming Short-Circuit in Lead-Free CH3NH3SnI3 Perovskite Solar Cells via Kinetically Controlled Gas-Solid Reaction Film Fabrication Process", J. Phys. Chem. Lett. 2016, 7, 776. Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have found that an electronic device having a semiconductor layer containing a doped semiconductor compound may have a decrease in photoelectric conversion efficiency over time. For example, when PTAA doped with TPFB as described in Non-Patent Document 1 is used in the buffer layer of a photoelectric conversion element, it has been found that although the initial photoelectric conversion efficiency is high, the photoelectric conversion efficiency rapidly decreases when stored under high temperature and high humidity. In order to put photoelectric conversion elements into practical use, it is necessary to improve the durability of the photoelectric conversion efficiency and make it difficult for the photoelectric conversion efficiency to decrease.

[0005] The present invention aims to improve the durability of an electronic device including a semiconductor layer. [Means for solving the problem]

[0006] The present inventors have discovered that the durability of an electronic device using a semiconductor compound can be improved by treating the semiconductor compound under specific conditions when doping the semiconductor compound, and have completed the present invention based on this discovery.

[0007] That is, the gist of the present invention lies in the following. [1] A method for producing an electronic device having a semiconductor layer, comprising: heating a coating solution containing an organic semiconductor compound and a dopant for the organic semiconductor compound, which is a hypervalent iodine compound, to 85° C. or higher. After By applying the coating liquid to Carrier mobility is 1.0x10 -4 cm 2 / V s or more The method includes the step of forming the semiconductor layer. the organic semiconductor compound is a triarylamine polymer whose repeating unit contains a triarylamine structure; the dopant is a diaryliodonium salt, and each of the aryl groups in the diaryliodonium salt is an aryl group having 30 or less carbon atoms which may have a substituent; the electronic device is a solar cell element comprising a pair of electrodes composed of a lower electrode and an upper electrode, an active layer containing a perovskite compound and disposed between the pair of electrodes, and a buffer layer disposed between the pair of electrodes and the active layer, and the semiconductor layer is the buffer layer. , manufacturing method. [ 2 The buffer layer is a hole extraction layer. 1

[0033] A manufacturing method according to the present invention. [ 3 The buffer layer is located between the upper electrode and the active layer. 1 ] or [ 2

[0033] A manufacturing method according to the present invention. Effect of the Invention

[0008] The durability of an electronic device including a semiconductor layer can be improved. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view that illustrates a schematic diagram of a photoelectric conversion element according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a schematic diagram of a solar cell according to an embodiment. [Diagram 3] 1 is a cross-sectional view illustrating a schematic diagram of a solar cell module according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following is a detailed description of the embodiments of the present invention. The following description of the components is an example (representative example) of the embodiments of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0011] The present invention relates to a method for producing an electronic device having a semiconductor layer. The production method according to the present invention includes a step of forming a semiconductor layer by heating a coating liquid containing an organic semiconductor compound and a dopant for the organic semiconductor compound, which is a hypervalent iodine compound, to 85° C. or higher and / or irradiating the coating liquid with ultraviolet light, and then coating the coating liquid. The following also describes the coating liquid for forming a semiconductor layer used in the step of forming the semiconductor layer, the production method thereof, and the electronic device produced by this production method.

[0012] [Organic semiconductor compounds] A semiconductor compound refers to a compound that can be used as a semiconductor material that exhibits semiconductor properties. In this specification, the term "semiconductor" is defined by the magnitude of carrier mobility in a solid state. As is well known, carrier mobility is an index that indicates how fast (or how much) charges (electrons or holes) can be moved. Specifically, in this specification, a "semiconductor" is a compound that has a carrier mobility of preferably 1.0x10 at room temperature.-6 cm 2 / V s or more, preferably 1.0x10 -5 cm 2 / V s or more, preferably 5.0x10 -5 cm 2 / V s or more, preferably 1.0x10 -4 cm 2 / V·s or more. The carrier mobility can be measured, for example, by measuring the IV characteristics of a field-effect transistor or by the time-of-flight method.

[0013] In this embodiment, an organic semiconductor compound is used as the semiconductor compound, but the type is not particularly limited, and for example, a conventionally known compound can be used. As the organic semiconductor compound, low molecular weight compounds and polymeric compounds are known. As the low molecular weight organic semiconductor compound, polycyclic aromatic compounds can be mentioned, and specific examples thereof include acene compounds such as tetracene or pentacene, oligothiophene compounds, phthalocyanine compounds, perylene compounds, rubrene compounds, or arylamine compounds such as triarylamine compounds. In addition, as the polymeric organic semiconductor compound, conjugated polymers such as polythiophene-based polymers, polyacetylene-based polymers, polyaniline-based polymers, polyphenylene-based polymers, polyphenylenevinylene-based polymers, polyfluorene-based polymers, or polypyrrole-based polymers, or arylamine polymers such as triarylamine polymers can be mentioned.

[0014] The organic semiconductor compound is preferably an arylamine compound, more preferably a triarylamine compound. The arylamine compound is a compound having an arylamine structure (a bond between an aryl group and a nitrogen atom), including an arylamine polymer. The arylamine polymer is a polymer whose repeating unit contains an arylamine structure. The triarylamine compound is a compound having a triarylamine structure (a bond between three aryl groups and the same nitrogen atom), including a triarylamine polymer. The triarylamine polymer is a polymer whose repeating unit contains a triarylamine structure. Such an arylamine compound or triarylamine compound is preferred in that it can be stably oxidized by a dopant and exhibits good semiconductor properties.

[0015] Here, the aryl group (or aromatic group) refers to an aromatic hydrocarbon group or an aromatic heterocyclic group, including a monocyclic group, a condensed ring group, and a group in which a monocyclic ring or a condensed ring is linked. The aromatic group is not particularly limited, but preferably has 30 or less carbon atoms, more preferably has 12 or less carbon atoms. Specific examples of aromatic hydrocarbon groups include a phenyl group, a naphthyl group, and a biphenyl group. Specific examples of aromatic heterocyclic groups include a thienyl group, a furyl group, a pyrrolyl group, a pyridyl group, and an imidazolyl group.

[0016] The aromatic group may have a further substituent. The substituent that the aromatic group may have is not particularly limited, and examples thereof include a halogen atom, a hydroxyl group, a cyano group, an amino group, a carboxyl group, an ester group, an alkylcarbonyl group, an acetyl group, a sulfonyl group, a silyl group, a boryl group, a nitrile group, an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, a thio group, a seleno group, an aromatic hydrocarbon group, and an aromatic heterocyclic group. The substituent that the aryl group has is preferably an amino group or an alkyl group having 1 to 6 carbon atoms. Here, the amino group is preferably a dialkylamino group having 2 to 12 carbon atoms, an alkylarylamino group having 7 to 20 carbon atoms, or a diarylamino group having 12 to 30 carbon atoms.

[0017] Preferred examples of the organic semiconductor compound include compounds represented by the following formula (I) or (II). [ka]

[0018] In formula (I) and (II), Ar 1 is a divalent aromatic group, Ar 2 is a direct bond or a divalent aromatic group. 1 and Ar 2 and may be the same or different. A divalent aromatic group is a substituent obtained by removing one hydrogen atom from the aromatic group described above. Ar 1 and Ar 2 are each independently preferably a divalent aromatic group having 2 to 20 carbon atoms, more preferably an aromatic hydrocarbon group having 6 to 20 carbon atoms (including a monocyclic ring, a condensed ring, and a ring in which a monocyclic ring or a condensed ring is linked). These divalent aromatic groups preferably have no further substituent or have an alkyl group having 1 to 6 carbon atoms.

[0019] In formula (I) and (II), Ar 3 ~Ar 5 is an aromatic group which may have a substituent. As the aromatic group, those described above can be used. Ar 3 ~Ar 5 may be the same or different aromatic groups. 3 ~Ar 5 are each independently preferably an aromatic group having 2 to 20 carbon atoms, more preferably an aromatic hydrocarbon group having 6 to 20 carbon atoms (including monocyclic rings, condensed rings, and those in which monocyclic or condensed rings are linked). These aromatic groups preferably have no further substituents, or have the above-mentioned amino group or alkyl group having 1 to 6 carbon atoms.

[0020] Specific examples of the organic semiconductor compound include the following compounds:

[0021] [ka]

[0022] [ka]

[0023] [Dopant] In this embodiment, a hypervalent iodine compound is used as a dopant. The hypervalent iodine compound acts as a dopant for an organic semiconductor compound. It is known that the hypervalent iodine compound exhibits electron-accepting properties (i.e., acts as an oxidizing agent). In addition, the electron-accepting dopant can improve the conductivity or hole transport ability of the semiconductor compound by removing electrons from the semiconductor compound. In this way, the hypervalent iodine compound can improve the charge transport properties of the semiconductor compound used in the electronic device.

[0024] A hypervalent iodine compound is a compound containing hypervalent iodine, and is defined as a compound containing iodine with an oxidation number of +3 or more. For example, the dopant can be an iodine(III) compound or an iodine(V) compound. An iodine(V) compound containing pentavalent iodine can be a periodinane compound such as Dess-Martin periodinane. In addition, an iodine(III) compound containing trivalent iodine can be a compound having a structure in which iodobenzene is oxidized, such as (diacetoxyiodo)benzene, or a diaryliodonium salt. It is preferable to use a diaryliodonium salt because it shows good electron acceptance and is less likely to cause a reverse reaction if the molecule is destroyed during the oxidation process.

[0025] Diaryliodonium salts are compounds in which the + -Ar]X -Here, each of the two Ar represents an aryl group. The aryl group (aromatic group) is not particularly limited, and may be, for example, any of those already listed for the organic semiconductor compound. X - represents any anion. X - Examples of the cations include halide ions, trifluoroacetate ions, tetrafluoroborate ions, and tetrakis(pentafluorophenyl)borate ions. X is preferred because it has high solubility and allows the reaction for producing the coating solution to proceed smoothly. - is preferably an anion having a fluorine atom.

[0026] A preferred example of the dopant is represented by the general formula (III). In the formula (III), X - represents any anion, specific examples of which are as described above. [ka]

[0027] In formula (III), R 1 and R 2 are each independently a monovalent organic group. Examples of the monovalent organic group include an aliphatic group or an aromatic group. Examples of the aliphatic group include an aliphatic hydrocarbon group having 1 to 20 carbon atoms or an aliphatic heterocyclic group having 4 to 20 carbon atoms. For example, the aliphatic group may be an alkyl group including a cycloalkyl group, an alkenyl group, or an alkynyl group, and specific examples thereof include a methyl group, an ethyl group, a butyl group, a cyclohexyl group, or a tetrahydrofuryl group.

[0028] Examples of the aromatic group include an aromatic hydrocarbon group having 6 to 20 carbon atoms and an aromatic heterocyclic group having 2 to 20 carbon atoms. For example, the aromatic group includes a phenyl group, a naphthyl group, a biphenyl group, a thienyl group, a pyridyl group, and the like.

[0029] The aliphatic and aromatic groups may have a substituent, which is not particularly limited and may include a halogen atom, a hydroxyl group, a cyano group, an amino group, a carboxyl group, an ester group, an alkylcarbonyl group, an acetyl group, a sulfonyl group, a silyl group, a boryl group, a nitrile group, an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, a thio group, a seleno group, an aromatic hydrocarbon group, and an aromatic heterocyclic group.

[0030] R 1 and R 2 R is preferably an aromatic hydrocarbon group having 6 to 20 carbon atoms, more preferably a phenyl group. Here, it is preferable that the aromatic hydrocarbon group does not have a substituent or has an alkyl group having 1 to 6 carbon atoms. 1 and R 2 is particularly preferably a phenyl group having an alkyl group at the para position.

[0031] [Preparation of coating solution] In this embodiment, a coating liquid containing an organic semiconductor compound and a dopant for the organic semiconductor compound, which is a hypervalent iodine compound, is heated to 85° C. or higher and / or this coating liquid is irradiated with ultraviolet light, thus preparing a coating liquid for forming a semiconductor layer. For example, first, a solution containing an organic semiconductor compound and a dopant for the organic semiconductor compound, which is a hypervalent iodine compound, is prepared. Next, the prepared solution is heated to 85° C. or higher and / or this solution is irradiated with ultraviolet light. In this way, a coating liquid for forming a semiconductor layer can be produced.

[0032] First, a solution containing an organic semiconductor compound and a dopant is prepared. Specifically, the organic semiconductor compound and the dopant are dissolved in a solvent. However, it is not necessary to completely dissolve these compounds in the solvent, and the compounds may be dissolved in the solvent when heating or irradiating with ultraviolet light is performed.

[0033] The solvent used is a solvent capable of dissolving the semiconductor compound and the dopant. In addition, a solvent having a boiling point higher than the temperature at which the solution is prepared is preferably used. Examples of the solvent include aliphatic hydrocarbons such as heptane, octane, isooctane, nonane, or decane; aromatic hydrocarbons such as toluene, xylene, mesitylene, cumene, tetralin, cyclohexylbenzene, fluorobenzene, chlorobenzene, bromobenzene, or orthodichlorobenzene; alicyclic hydrocarbons such as methylcyclohexane, cycloheptane, cyclooctane, or decalin; aliphatic ketones such as cyclopentanone or cyclohexanone; aromatic ketones such as acetophenone or propiophenone; esters such as butyl acetate, methyl lactate, methyl benzoate, ethyl benzoate, isopropyl benzoate, isobutyl benzoate, or isoamyl benzoate; halogenated hydrocarbons such as trichloroethylene; or ethers such as cyclopentyl methyl ether, anisole, diphenyl ether, dimethoxyethane, or dioxane.

[0034] Next, the prepared solution is heated to 85°C or higher, or the solution is irradiated with ultraviolet light, or both of these are performed. When heating, the heating method is not particularly limited, and for example, a heat source such as a hot plate or a heated atmosphere such as an oven may be used. When irradiating with ultraviolet light, the irradiation method is not particularly limited, and for example, an ultraviolet lamp may be used. The solution may be stirred during heating or ultraviolet light irradiation. In the present invention, ultraviolet light refers to light having a wavelength in the range of 200 nm or more and less than 400 nm.

[0035] According to the study by the present inventors, the durability of an electronic device having a semiconductor layer formed using the obtained coating liquid for forming a semiconductor layer is improved by heating to 85° C. or higher or by irradiating with ultraviolet light. The reason for this is not clear, but the present inventors believe that a chemical change occurs in the organic semiconductor compound in the solution by heating to 85° C. or higher or by irradiating with ultraviolet light.

[0036] It has been known that even if a coating liquid for forming a semiconductor layer is prepared by heating at 70°C or less as in the conventional method, an electronic device having a semiconductor layer formed using the coating liquid for forming a semiconductor layer functions. However, the present inventors have found that the electronic device thus prepared loses performance in a short period of time under a high-temperature and high-humidity environment. The present inventors presume that the reason for this is that even in the conventional method, charge transfer from the semiconductor compound to the dopant occurs, so that the semiconductor layer initially exhibits charge transport properties, but the oxidation state of the semiconductor compound is unstable, so that the charge of the dopant is likely to return to the semiconductor compound under a high-temperature and high-humidity environment. As a result, the semiconductor layer becomes electrically neutral, so the conductivity decreases, and the performance of the electronic device decreases.

[0037] On the other hand, the inventors of the present application presume that heating to 85°C or higher or irradiating with ultraviolet light causes the organic semiconductor compound to be oxidized by a chemical reaction between the dopant and the organic semiconductor compound, so that the organic semiconductor compound becomes stable in the oxidized state, making it difficult for the charge of the semiconductor layer to return to the dopant again. For example, if a reaction occurs in which the dopant is broken down by high temperature, and an active oxidizing agent is generated, resulting in the organic semiconductor compound being oxidized, it is considered that the reaction in which the organic semiconductor compound acquires charge again is unlikely to proceed.

[0038] In particular, since reactions generally proceed easily in a solution state, it is expected that the reaction between the dopant and the organic semiconductor compound will proceed smoothly by heating to 85°C or higher or by irradiating with ultraviolet light. On the other hand, even if the temperature is raised when a semiconductor layer is formed by applying a coating liquid for forming a semiconductor layer and drying the applied semiconductor layer, it is expected that the reaction will not proceed smoothly in a solid state. In this embodiment, by heating to 85°C or higher or irradiating with ultraviolet light in a solution state, it is considered that a semiconductor layer having sufficiently high conductivity and thermodynamic stability is formed even when the semiconductor layer is applied and formed into a film at a low temperature that does not damage the electronic device.

[0039] In one embodiment, the amount of unreacted dopant contained in the coating liquid for forming a semiconductor layer is 80% by mass or less of the amount of dopant. Here, the amount of dopant is the sum of the amount of unreacted dopant and the amount of reacted dopant. The unreacted dopant refers to a dopant that has not undergone a chemical reaction with an organic semiconductor compound and has not been broken, so that the charge it has can be returned to the organic semiconductor compound. The reacted dopant refers to a decomposition product of a dopant that has been broken through a chemical reaction with an organic semiconductor compound and does not have the ability to give a charge to the organic semiconductor compound again. In another embodiment, the amount of dopant refers to the amount of dopant used to prepare the coating liquid for forming a semiconductor layer.

[0040] As described above, if the chemical reaction between the organic semiconductor compound and the dopant has progressed to a certain extent, the phenomenon in which the semiconductor layer loses its charge transport properties is unlikely to occur, and it is considered that the chemical reaction between the organic semiconductor compound and the dopant has progressed completely, resulting in a semiconductor layer with higher durability. From this viewpoint, the amount of unreacted dopant contained in the coating liquid for forming a semiconductor layer is preferably 60% by mass or less of the amount of dopant, more preferably 40% by mass or less, even more preferably 20% by mass or less, and particularly preferably substantially absent. The amount of unreacted dopant can be confirmed by chemical analysis, and can also be estimated by a quantitative method using ultraviolet-visible absorption spectrum.

[0041] From the viewpoint of sufficiently proceeding with the reaction, the temperature of the solution during heating is preferably 90° C. or higher, more preferably 95° C. or higher, even more preferably 100° C. or higher, more preferably 115° C. or higher, even more preferably 135° C. or higher, and particularly preferably 150° C. or higher. On the other hand, in order to prevent decomposition of the compound semiconductor, the temperature is preferably equal to or lower than the thermal decomposition temperature of the semiconductor compound. In the present invention, the thermal decomposition temperature means the temperature at which the mass is reduced by 5% when measured by TG-DTA.

[0042] From the viewpoint of sufficiently promoting the reaction, the heating time is preferably 10 minutes or more, more preferably 20 minutes or more, and even more preferably 30 minutes or more. The upper limit of the time is not particularly limited, but may be, for example, 10 hours or less.

[0043] When irradiating with ultraviolet light, the solution containing the organic semiconductor compound and the dopant is irradiated with 0.1 J / cm 2 By irradiating the ultraviolet light at a dose of 0.5 J / cm or more, the chemical reaction can be sufficiently promoted. 2 More preferably, 1 J / cm 2 On the other hand, to prevent the decomposition of semiconductor compounds, the ultraviolet light dose is 1000 J / cm 2 It is preferably equal to or less than 800 J / cm. 2 Less than 500 J / cm, more preferably 500 J / cm 2 There is no particular limit to the ultraviolet light intensity, but for example, 5 mW / cm at 365 nm. 2 The ultraviolet light source is not particularly limited, but a mercury lamp or a metal halide lamp can be used.

[0044] The coating liquid for forming a semiconductor layer may be heated to 85° C. or higher and irradiated with ultraviolet light. For example, the coating liquid for forming a semiconductor layer may be heated to 85° C. or higher and then irradiated with ultraviolet light, or the coating liquid for forming a semiconductor layer may be irradiated with ultraviolet light and then heated to 85° C. or higher. The coating liquid for forming a semiconductor layer may be heated to 85° C. or higher and irradiated with ultraviolet light at the same time. As reaction conditions in these cases, the above-mentioned conditions may be appropriately adjusted and used so that the reaction between the dopant and the semiconductor compound can proceed smoothly.

[0045] The concentrations of the organic semiconductor compound and the dopant in the coating liquid are not particularly limited and can be appropriately set according to the desired thickness of the semiconductor layer, etc. For example, the concentration of the organic semiconductor compound in the coating liquid may be 1.0% by mass or more and 10% by mass or less. In addition, the amount of the dopant in the coating liquid may be 1.0% by mass or more and 20% by mass or less with respect to the amount of the organic semiconductor compound in the coating liquid.

[0046] [Application of coating liquid] In this embodiment, the semiconductor layer is formed by applying the coating solution prepared as above. Any method can be used as the coating method of the coating solution, and examples of the method include spin coating, inkjet, doctor blade, drop casting, reverse roll coating, gravure coating, kiss coating, roll brush, spray coating, air knife coating, wire barber coating, pipe doctor, impregnation coating, curtain coating, etc.

[0047] After the coating liquid is applied, it can be dried by heating. The heating temperature at this time is not particularly limited, but from the viewpoint of sufficiently removing the solvent, it is preferably 60°C or higher, more preferably 80°C or higher. On the other hand, in order to suppress damage to the electronic device, it is preferable that the heating temperature is lower than the temperature at the time of preparing the coating liquid. Specifically, the heating temperature is preferably less than 150°C, more preferably less than 135°C, more preferably less than 115°C, more preferably less than 100°C, more preferably less than 95°C, more preferably less than 90°C, and particularly preferably less than 85°C. There is no particular limit to the heating time, but from the viewpoint of sufficiently removing the solvent, it is preferably 1 minute or more, more preferably 3 minutes or more, while from the viewpoint of improving the production efficiency, it is preferably 10 hours or less, more preferably 1 hour or less. These heatings may be performed under normal pressure or under reduced pressure.

[0048] The thickness of the semiconductor layer is not particularly limited and can be appropriately selected depending on the application of the semiconductor layer. For example, the thickness of the semiconductor layer may be 0.5 nm or more and 500 nm or less.

[0049] [Electronic Devices] The type of electronic device is not particularly limited. In this specification, the electronic device refers to a device having two or more electrodes and controlling the current flowing between the electrodes or the voltage generated between the electrodes by electricity, light, magnetism, chemical substances, etc., or a device that generates light, an electric field, a magnetic field, etc. by the voltage or current applied between the electrodes. Specific examples include an element that controls the current or voltage by applying a voltage or current, an element that controls the voltage or current by applying a magnetic field, or an element that controls the voltage or current by acting on a chemical substance. Specific examples of control include rectification, switching, amplification, and oscillation.

[0050] Examples of electronic devices include resistors, rectifiers (diodes), switching elements (transistors, thyristors), amplifying elements (transistors), memory elements, chemical sensors, etc., or semiconductor devices obtained by combining or integrating these elements. Further examples of electronic devices include optical elements, including photodiodes or phototransistors that generate photocurrent, electroluminescent elements that emit light when an electric field is applied, or photoelectric conversion elements or solar cells that generate electromotive force when light is applied. More specific examples of semiconductor devices include those described in Physics of Semiconductor Devices, 2nd Edition (Wiley Interscience 1981) by SMSe.

[0051] The electronic device according to the present embodiment includes a semiconductor layer, but the specific configuration is not particularly limited. In one embodiment, the electronic device has a pair of electrodes and a semiconductor layer disposed between the pair of electrodes. The semiconductor layer is obtained by applying the semiconductor layer forming coating liquid according to the present embodiment. The type of the electrode is not particularly limited. The electrode can be produced using an appropriate material depending on the type of the electronic device.

[0052] Preferred examples of electronic devices include electroluminescent elements (LEDs), photoelectric conversion elements, and solar cells. For example, an electroluminescent element (LED) according to an embodiment can include a pair of electrodes, an anode and a cathode, a light-emitting layer disposed between the electrodes, and a semiconductor layer disposed between the light-emitting layer and one of the electrodes. In an embodiment, a semiconductor layer obtained by applying the semiconductor layer-forming coating liquid according to the present embodiment is provided as a hole transport layer between the light-emitting layer and the anode.

[0053] As described above, in this embodiment, the electronic device is manufactured by a manufacturing method including a step of forming a semiconductor layer by applying the coating liquid prepared as described above. The manufacturing method of the electronic device according to this embodiment is not particularly limited and can be appropriately determined according to the configuration of the electronic device. For example, the electronic device can be manufactured by a step of forming a semiconductor layer by applying a coating liquid onto a substrate on which an electrode is formed, and a step of forming an electrode on the semiconductor layer.

[0054] After the semiconductor layer is formed, for example, after each element constituting the electronic device is formed, the electronic device can be heated. This step is sometimes called an annealing process, and the effect of improving the adhesion between each element constituting the electronic device and improving the performance of the electronic device can be obtained. The heating temperature at this time is not particularly limited, but from the viewpoint of obtaining a sufficient adhesion improvement effect, it is preferably 50 ° C or more, more preferably 80 ° C or more. In addition, it is preferable to heat in a temperature range of preferably 300 ° C or less, more preferably 280 ° C or less, more preferably 250 ° C or less. On the other hand, in order to suppress damage to the electronic device, it is preferable that the heating temperature is lower than the temperature at the time of preparing the coating liquid. Specifically, the heating temperature is preferably less than 150 ° C, more preferably less than 135 ° C, more preferably less than 115 ° C, more preferably less than 100 ° C, even more preferably less than 95 ° C, more preferably less than 90 ° C, and particularly preferably less than 85 ° C. The heating time is not particularly limited, but from the viewpoint of obtaining a sufficient effect of improving adhesion, it is preferably 1 minute or more, more preferably 3 minutes or more, while from the viewpoint of improving production efficiency, it is preferably 180 minutes or less, more preferably 60 minutes or less. The heating may be performed under normal pressure or under reduced pressure.

[0055] Hereinafter, as a preferred example of the electronic device, a photoelectric conversion element including a semiconductor layer will be described.

[0056] [Photoelectric conversion element] The photoelectric conversion element according to the present embodiment includes a pair of electrodes composed of a lower electrode and an upper electrode, an active layer between the pair of electrodes, and a buffer layer between the pair of electrodes and the active layer. In one embodiment, the buffer layer is a semiconductor layer obtained by applying the semiconductor layer-forming coating liquid according to the present embodiment.

[0057] FIG. 1 is a cross-sectional view showing a schematic diagram of an embodiment of a photoelectric conversion element according to the present invention. The photoelectric conversion element shown in FIG. 1 is a photoelectric conversion element used in a general thin-film solar cell, but the photoelectric conversion element according to the present invention is not limited to the one shown in FIG. 3. The photoelectric conversion element 100 according to one embodiment of the present invention has a layer structure in which a base material 108, a lower electrode 101, a buffer layer 102, an active layer 103, a buffer layer 105, and an upper electrode 107 are formed in this order. As shown in FIG. 3, when the photoelectric conversion element 100 has a structure in which each layer is laminated on the base material 108, the electrode closer to the base material 108 can be called the lower electrode 101, and the electrode farther from the base material 108 can be called the upper electrode 107. It is not necessary to provide both the buffer layer 102 and the buffer layer 105.

[0058] Furthermore, the photoelectric conversion element 100 may further include other layers. Examples of the other layers include a work function tuning layer that adjusts the work function of the lower electrode 101 or the upper electrode 107, an insulating layer, and the like.

[0059] The semiconductor layer obtained by applying the coating liquid for forming a semiconductor layer according to this embodiment can exhibit good hole transport properties, and therefore can be preferably used as a hole extraction layer. For example, in one embodiment, one of the lower electrode 101 and the upper electrode 107 is a cathode, and the other is an anode. In one embodiment, the lower electrode 101 is a cathode, in which case the buffer layer 102 is an electron extraction layer, the buffer layer 105 is a hole extraction layer, and the upper electrode 107 is an anode. In such a configuration, the buffer layer 105 (hole extraction layer) located between the upper electrode 107 and the active layer 103 can be a semiconductor layer obtained by applying the coating liquid for forming a semiconductor layer according to the present embodiment. In one embodiment, the lower electrode 101 is an anode, in which case the buffer layer 102 is a hole extraction layer, the buffer layer 105 is an electron extraction layer, and the upper electrode 107 is a cathode. In such a configuration, the buffer layer 102 (hole extraction layer) can be a semiconductor layer obtained by applying the coating liquid for forming a semiconductor layer according to this embodiment.

[0060] Furthermore, the semiconductor layer obtained by applying the coating liquid for forming a semiconductor layer according to this embodiment can exhibit high durability, and can therefore be preferably used as the buffer layer 105 located between the upper electrode 107 and the active layer 103 and susceptible to external influences.

[0061] (1.Active layer 103) The active layer 103 is a layer where photoelectric conversion takes place. When the photoelectric conversion element 100 receives light, the light is absorbed by the active layer 103 and carriers are generated. The generated carriers are extracted from the lower electrode 101 and the upper electrode 107.

[0062] The type of active layer 103 is not particularly limited, and a conventionally known type can be used. For example, the active layer 103 can be a heterojunction type active layer including a layer containing a p-type semiconductor compound such as a porphyrin derivative and a layer containing a fullerene derivative n-type semiconductor compound. The active layer 103 can also be a bulk heterojunction type active layer having a layer (i-layer) in which a p-type semiconductor compound and an n-type semiconductor compound are mixed. The active layer 103 can also be a layer containing a perovskite compound.

[0063] Preferably, the active layer 103 is a layer containing a perovskite compound. A solar cell having such an active layer 103 is known as a perovskite solar cell. In a perovskite semiconductor, a perovskite compound having a perovskite structure forms a crystal. In such a crystal, fast charge separation occurs and the diffusion distance of holes and electrons is long, so that efficient charge separation occurs. The present invention is particularly effective in the manufacture of a photoelectric conversion element using an active layer containing a perovskite compound. The reason for this is that a perovskite compound is usually insoluble in a solvent used in the coating liquid for forming the semiconductor layer, and a layer formed by the coating liquid for forming the semiconductor layer is insoluble in a solvent used to form a layer containing a perovskite compound, so that each layer can be laminated by a coating process without deterioration.

[0064] The perovskite compound refers to a semiconductor compound having a perovskite structure. The perovskite compound is not particularly limited, and may be selected from those listed in Galasso et al. Structure and Properties of Inorganic Solids, Chapter 7 - Perovskite type and related structures. For example, the perovskite compound may be represented by the general formula AMX3 or the general formula A2MX4. Here, M represents a divalent cation, A represents a monovalent cation, and X represents a monovalent anion. The perovskite compound may be selected appropriately depending on the type of semiconductor device. As the perovskite compound, it is preferable to use a semiconductor compound having an energy band gap of 1.0 eV or more and 3.5 eV or less.

[0065] There is no particular limitation on the monovalent cation A, but those described in the above book by Galasso can be used. More specific examples include cations containing elements of Groups 1 and 13 to 16 of the periodic table. Among these, cesium ion, rubidium ion, ammonium ion (including amidinium ion) which may have a substituent, phosphonium ion which may have a substituent, or amidinium ion which may have a substituent are preferred. Examples of ammonium ions which may have a substituent include primary ammonium ions and secondary ammonium ions. There is no particular limitation on the substituent. Specific examples of ammonium ions which may have a substituent include alkylammonium ions, arylammonium ions, amidinium ions, and guanidium ions. In particular, in order to avoid steric hindrance, monoalkylammonium ions which form a three-dimensional crystal structure are preferred, and from the viewpoint of improving stability, it is preferred to use alkylammonium ions substituted with one or more fluorine groups. In addition, a combination of two or more types of cations can be used as the cation A.

[0066] Specific examples of the monovalent cation A include a methylammonium ion, a methylammonium monofluoride ion, a methylammonium difluoride ion, a methylammonium trifluoride ion, an ethylammonium ion, an isopropylammonium ion, an n-propylammonium ion, an isobutylammonium ion, an n-butylammonium ion, a t-butylammonium ion, a dimethylammonium ion, a diethylammonium ion, a phenylammonium ion, a benzylammonium ion, a phenethylammonium ion, a guanidinium ion, a formamidinium ion, an acetamidinium ion, and an imidazolium ion.

[0067] There is no particular limitation on the divalent cation M, but it is preferably a divalent metal cation or semimetal cation. Specific examples include cations of elements in Group 14 of the periodic table, and more specific examples include lead cations (Pb 2+ ), tin cation (Sn 2+ ), germanium cation (Ge 2+ ) can be mentioned. In addition, a combination of two or more kinds of cations can be used as the cation M. From the viewpoint of obtaining a stable photoelectric conversion element, it is particularly preferable to use a lead cation or two or more kinds of cations including a lead cation.

[0068] Examples of monovalent anions X include halide ions, acetate ions, nitrate ions, sulfate ions, borate ions, acetylacetonate ions, carbonate ions, citrate ions, sulfur ions, tellurium ions, thiocyanate ions, titanate ions, zirconate ions, 2,4-pentanedionate ions, and silicofluoride ions. In order to adjust the band gap, X may be one type of anion or a combination of two or more types of anions. Among them, it is preferable to use a halide ion or a combination of a halide ion and another anion as X. Examples of halide ions X include chloride ions, bromide ions, and iodide ions.

[0069] Preferred examples of the perovskite compound include organic-inorganic perovskite compounds, particularly halide-based organic-inorganic perovskite compounds. Specific examples of the perovskite compound include CH3NH3PbI3, CH3NH3PbBr3, CH3NH3PbCl3, CH3NH3SnI3, CH3NH3SnBr3, CH3NH3SnCl3, CH3NH3PbI (3-x) Cl x , CH3NH3PbI (3-x) Br x , CH3NH3PbBr (3-x) Cl x , CH3NH3Pb (1-y) Sn y I3, CH3NH3Pb (1-y) Sn y Br3, CH3NH3Pb (1-y) Sn y Cl3, CH3NH3Pb (1-y) Sn y I (3-x) Cl x , CH3NH3Pb (1-y) Sn y I (3-x) Br x , and CH3NH3Pb (1-y) Sn y Br (3-x) Cl x and the above compounds in which CFH2NH3, CF2HNH3, CF3NH3, NH2CH=NH2 are used instead of CH3NH3. Here, x is an arbitrary value of 0 or more and 3 or less, and y is an arbitrary value of 0 or more and 1 or less.

[0070] The active layer 103 may contain two or more types of perovskite compounds. For example, the active layer 103 may contain two or more types of perovskite compounds in which at least one of A, B, and X is different.

[0071] The amount of the perovskite compound contained in the active layer 103 is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, so as to obtain good semiconductor characteristics. There is no particular upper limit.

[0072] There is no particular limit to the thickness of the active layer 103. In terms of being able to absorb more light, the thickness of the active layer 103 is preferably 5 nm or more, more preferably 10 nm or more, even more preferably 50 nm or more, and particularly preferably 120 nm or more. On the other hand, in terms of reducing the series resistance, the thickness of the active layer 103 is preferably 2000 nm or less, and more preferably 1000 nm or less.

[0073] There is no particular limitation on the method for forming the active layer 103, and any method can be used. Specific examples include a coating method and a vapor deposition method (or a co-evaporation method). The coating method is preferable because it allows the active layer 103 to be easily formed.

[0074] An example of a method for producing the active layer 103 containing a perovskite compound is, for example, a method of forming a semiconductor layer by applying a coating liquid containing a perovskite compound or a precursor thereof. The perovskite compound precursor refers to a material that can be converted into a perovskite compound after the coating liquid is applied. A specific example is a perovskite compound precursor that can be converted into a perovskite compound by heating. For example, by heating a film obtained by applying a coating liquid, the perovskite compound precursor can be converted into a perovskite compound to form a semiconductor layer containing a perovskite compound. A specific example of the perovskite compound precursor is a compound represented by the following formula (2) and / or a compound represented by the following formula (3), which can be converted into a perovskite compound represented by the following formula (1) by heating.

[0075] One example is a method of preparing a coating liquid containing a compound represented by the following formula (2), a compound represented by the following formula (3), and a solvent, and coating the coating liquid. Such a coating liquid can be prepared by heating and stirring the compounds in a solution. According to this method, an active layer 103 containing a compound represented by the following formula (1) can be prepared.

[0076] AMX3···(1) AX ···(2) MX2···(3) The definitions of A, M, and X are as described above. Specific examples of AX include alkyl ammonium halide salts, and specific examples of MX2 include metal halides. AX and MX2 are precursors of the perovskite semiconductor compound AMX3.

[0077] Another example is a method of preparing and applying a coating liquid containing a compound represented by the above formula (2) and a solvent, and a coating liquid containing a compound represented by the above formula (3) and a solvent. For example, a layer of the compound represented by formula (3) is formed by applying a coating liquid containing a compound represented by formula (3) and a solvent. An active layer 103 containing a compound represented by the following formula (1) can be produced by applying a coating liquid containing a compound represented by formula (2) and a solvent thereon. After applying each coating liquid, heating can be performed to dry the layer or promote crystallization of the perovskite semiconductor compound. Heating can be performed, for example, at 60°C or higher or 180°C or lower.

[0078] The solvent preferably has a solubility parameter (SP value) of 9 or more, particularly preferably 10 or more, as described in "Polymer Handbook, 4th Ed." edited by Brandrup, J. et al. Examples include N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylpyrrolidone, dimethylsulfoxide, pyridine, and γ-butyrolactone. A mixed solvent of two or more solvents may be used as the solvent. In addition, when a mixed solvent is used, it is preferable that at least one of the mixed solvents has a solubility parameter of 10 or more.

[0079] (2. Buffer layers 102, 105) The buffer layer can usually be classified into an electron extraction layer and a hole extraction layer. As described above, at least one of the buffer layers provided in the photoelectric conversion element 100 can be a semiconductor layer obtained by applying the semiconductor layer forming coating liquid according to the present embodiment. In addition, such a semiconductor layer is preferably used as a hole extraction layer. The buffer layer 102 may be a hole extraction layer and the buffer layer 105 may be an electron extraction layer, or the buffer layer 102 may be an electron extraction layer and the buffer layer 105 may be a hole extraction layer, but it is preferable that the buffer layer 105 is a buffer layer formed by applying the semiconductor layer forming coating liquid. The reason for this is that the perovskite precursor solution tends to have low wettability with respect to a layer formed using the semiconductor layer forming coating liquid, whereas the semiconductor layer forming composition tends to have high wettability with respect to an active layer containing a perovskite compound. In addition, when the electrode 107 is formed by a sputtering process, the layer formed by the semiconductor layer forming coating liquid tends to be less oxidized, and therefore is less susceptible to oxidation damage due to the sputtering process. The hole extraction layer and the electron extraction layer will be described below. Note that one buffer layer may be composed of a plurality of different films.

[0080] The material of the hole extraction layer is not particularly limited, as long as it is a material capable of improving the efficiency of extracting holes from the active layer 103 to the anode. As described above, it is preferable to use a semiconductor layer obtained by applying the semiconductor layer forming coating liquid according to this embodiment as the hole extraction layer. Other examples of the material of the hole extraction layer include inorganic compounds or organic compounds described in known documents such as WO 2013 / 171517, WO 2013 / 180230, or JP 2012-191194 A.

[0081] For example, inorganic compounds include metal oxides such as copper oxide, nickel oxide, manganese oxide, iron oxide, molybdenum oxide, vanadium oxide, tungsten oxide, etc. Also, organic compounds include conductive polymers (e.g., PEDOT:PSS or doped P3HT) in which polythiophene, polypyrrole, polyacetylene, triphenylenediamine, polyaniline, etc. are doped with sulfonic acid and iodine, polythiophene derivatives having sulfonyl groups as substituents, conductive organic compounds such as arylamine, Nafion, or lithium-doped spiro-OMeTAD.

[0082] The total thickness of the hole extraction layer is not particularly limited, but is preferably 0.5 nm or more. On the other hand, it is preferably 400 nm or less, and more preferably 200 nm or less. When the thickness of the hole extraction layer is 0.5 nm or more, it functions well as a buffer material, and when the thickness of the hole extraction layer is 400 nm or less, it becomes easy to extract holes, and the photoelectric conversion efficiency can be improved.

[0083] There is no limitation on the method for forming the hole extraction layer. When a sublimable compound is used, the hole extraction layer can be formed by a dry film formation method such as a vacuum deposition method. When a solvent-soluble compound is used, the hole extraction layer can be formed by a wet film formation method such as a spin coating method or an inkjet method.

[0084] The material of the electron extraction layer is not particularly limited as long as it is a material capable of improving the efficiency of extracting electrons from the active layer 103 to the cathode. Specific examples of the material include inorganic compounds, organic compounds, and organic-inorganic perovskite compounds described in publicly known documents such as WO 2013 / 171517, WO 2013 / 180230, and JP 2012-191194 A.

[0085] For example, inorganic compounds include salts of alkali metals such as lithium, sodium, potassium, or cesium, and metal oxides such as zinc oxide, titanium oxide, aluminum oxide, indium oxide, or tin oxide. Organic compounds include bathocuproine (BCP), bathophenanthrene (Bphen), (8-hydroxyquinolinato)aluminum (Alq3), boron compounds, oxadiazole compounds, benzimidazole compounds, naphthalenetetracarboxylic anhydride (NTCDA), perylenetetracarboxylic anhydride (PTCDA), fullerene compounds, and phosphine compounds having a double bond with an element of Group 16 of the periodic table, such as phosphine oxide compounds or phosphine sulfide compounds.

[0086] There is no particular limitation on the method for forming the electron extraction layer. When a sublimable compound is used as a material, the electron extraction layer can be formed by a dry film formation method such as a vacuum deposition method. When a solvent-soluble compound is used as a material, the electron extraction layer can be formed by a wet film formation method such as a spin coating method or an inkjet method.

[0087] The total thickness of the electron extraction layer is not particularly limited, but is preferably 0.5 nm or more, more preferably 1 nm or more, more preferably 5 nm or more, and particularly preferably 10 nm or more. On the other hand, it is preferably 1 μm or less, more preferably 700 nm or less, more preferably 400 nm or less, and particularly preferably 200 nm or less. When the thickness of the electron extraction layer 105 is within the above range, uniform coating is easy and the electron extraction function can be well exhibited.

[0088] (3.Electrode 101,107) The electrode has a function of collecting holes and electrons generated by light absorption. Therefore, it is preferable to use an anode suitable for collecting holes and a cathode suitable for collecting electrons as a pair of electrodes. Either one of the pair of electrodes may be light-transmitting, and both may be light-transmitting. Being light-transmitting means that 40% or more of sunlight passes through. In addition, it is preferable that the sunlight transmittance of the transparent electrode is 70% or more, so that more light passes through the transparent electrode and reaches the active layer 103. The light transmittance can be measured with a spectrophotometer (for example, U-4100 manufactured by Hitachi High-Tech Corporation).

[0089] There are no particular limitations on the constituent members of the anode and cathode and the manufacturing method thereof, and well-known techniques can be used. For example, members and manufacturing methods thereof described in publicly known documents such as WO 2013 / 171517, WO 2013 / 180230, or JP 2012-191194 A can be used.

[0090] (4. Base material 108) The photoelectric conversion element 100 usually has a substrate 108 that serves as a support. However, the photoelectric conversion element according to the present invention may not have the substrate 108. The material of the substrate 108 is not particularly limited as long as it does not significantly impair the effects of the present invention, and for example, materials described in publicly known documents such as WO 2013 / 171517, WO 2013 / 180230, or JP 2012-191194 A can be used.

[0091] (5. Method for producing photoelectric conversion element) The photoelectric conversion element 100 can be produced by forming each layer constituting the photoelectric conversion element 100 according to the above-mentioned method. In order to improve durability, the photoelectric conversion element 100 may be further sealed. For example, the photoelectric conversion element 100 can be sealed by further laminating a sealing plate on the upper electrode 107 and fixing the base material 108 and the sealing plate with an adhesive.

[0092] There is no particular limitation on the method of forming each layer constituting the photoelectric conversion element 100, and the layers can be formed by the sheet-to-sheet (Manyo) method or the roll-to-roll method. The roll-to-roll method is a method in which a flexible substrate wound in a roll is unwound and processed while being transported intermittently or continuously until it is wound up by a winding roll. The roll-to-roll method is capable of batch processing of long substrates on the order of kilometers, and is therefore more suitable for mass production than the sheet-to-sheet method. On the other hand, when attempting to form each layer by the roll-to-roll method, due to its structure, the film may be scratched or partially peeled off due to contact between the film formation surface and the roll.

[0093] The size of the roll that can be used in the roll-to-roll method is not particularly limited as long as it can be handled by the manufacturing device of the roll-to-roll method, but the upper limit of the outer diameter is preferably 5 m or less, more preferably 3 m or less, and more preferably 1 m or less. On the other hand, the lower limit is preferably 10 cm or more, more preferably 20 cm or more, and more preferably 30 cm or more. The upper limit of the outer diameter of the roll core is preferably 4 m or less, more preferably 3 m or less, and more preferably 0.5 m or less. On the other hand, the lower limit is preferably 1 cm or more, more preferably 3 cm or more, more preferably 5 cm or more, more preferably 10 cm or more, and particularly preferably 20 cm or more. It is preferable that these diameters are less than the above upper limit in terms of high handleability of the roll, and it is preferable that they are more than the lower limit in terms of low possibility that the layer formed in each process will be destroyed by bending stress. The lower limit of the width of the roll is preferably 5 cm or more, more preferably 10 cm or more, and more preferably 20 cm or more. On the other hand, the upper limit is preferably 5 m or less, more preferably 3 m or less, and more preferably 2 m or less. A width equal to or less than the upper limit is preferable in terms of ease of handling of the roll, while a width equal to or greater than the lower limit is preferable in terms of greater freedom in the size of the photoelectric conversion element 100 .

[0094] After the upper electrode 107 is laminated, the photoelectric conversion element 100 may be subjected to the above-mentioned annealing process. The annealing process is preferably performed at a temperature of 50° C. or higher, since it has the effect of improving the adhesion between the layers of the photoelectric conversion element 100. The improved adhesion between the layers may improve the thermal stability, durability, etc. of the photoelectric conversion element. In the annealing process, stepwise heating using different temperatures may be performed.

[0095] The annealing process is preferably terminated when the open circuit voltage, short circuit current, and fill factor, which are parameters of the solar cell performance, reach a certain value. In addition, the annealing process is preferably performed under normal pressure and in an inert gas atmosphere in order to prevent thermal oxidation of the constituent materials. As a heating method, the photoelectric conversion element may be placed on a heat source such as a hot plate, or the photoelectric conversion element may be placed in a heating atmosphere such as an oven. In addition, heating may be performed in a batch manner or a continuous manner.

[0096] (6. Photoelectric Conversion Characteristics) The photoelectric conversion characteristics of the photoelectric conversion element 100 can be obtained as follows. The photoelectric conversion element 100 is irradiated with light under AM1.5G conditions by a solar simulator at an irradiation intensity of 100 mW / cm. 2 The photoelectric conversion characteristics, such as photoelectric conversion efficiency (PCE), short-circuit current density (Jsc), open circuit voltage (Voc), fill factor (FF), series resistance, and shunt resistance, can be calculated from the obtained current-voltage curve.

[0097] The photoelectric conversion efficiency of the photoelectric conversion element 100 is not particularly limited, but is preferably 1% or more, more preferably 1.5% or more, and more preferably 2% or more. On the other hand, there is no particular upper limit, and the higher the better. In addition, there is no particular limit to the fill factor of the photoelectric conversion element 100, but is preferably 0.6 or more, more preferably 0.7 or more, and more preferably 0.9 or more. On the other hand, there is no particular upper limit, and the higher the better.

[0098] The photoelectric conversion element according to this embodiment is characterized by its high durability. In one embodiment, the photoelectric conversion efficiency retention rate after being placed in a test environment of 60° C. temperature and 90% humidity for one day is 60% or more, preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. For example, the retention rate can be calculated based on the initial photoelectric conversion efficiency immediately after the photoelectric conversion element is produced and the photoelectric conversion efficiency after the photoelectric conversion element is placed in the test environment. The retention rate can also be measured after sealing the photoelectric conversion element as described above. Here, the retention rate can be calculated as follows based on the photoelectric conversion efficiency before and after being placed in the test environment. Maintenance rate (%) = ((Photoelectric conversion efficiency after being placed in the test environment) / (Photoelectric conversion efficiency before being placed in the test environment)) x 100

[0099] In one embodiment, the retention rate of photoelectric conversion efficiency after being placed in a test environment of 60°C temperature and 90% humidity for 96 hours is 40% or more, preferably 60% or more, more preferably 80% or more, even more preferably 90% or more, and particularly preferably 95% or more.

[0100] (7. Solar Cells) The photoelectric conversion element 100 according to this embodiment is preferably used as a solar cell, particularly as a solar cell element of a thin-film solar cell. FIG. 2 is a cross-sectional view showing a schematic configuration of a solar cell according to one embodiment of the present invention, and FIG. 2 shows a thin-film solar cell, which is a solar cell according to one embodiment of the present invention. As shown in FIG. 2, the thin-film solar cell 14 according to this embodiment includes a weather-resistant protective film 1, an ultraviolet-cutting film 2, a gas barrier film 3, a getter material film 4, a sealing material 5, a solar cell element 6, a sealing material 7, a getter material film 8, a gas barrier film 9, and a back sheet 10, in this order. The thin-film solar cell 14 according to this embodiment has the photoelectric conversion element according to this embodiment as the solar cell element 6. Then, light is irradiated from the side where the weather-resistant protective film 1 is formed (lower side in FIG. 2), and the solar cell element 6 generates electricity. It is not necessary for the thin-film solar cell 14 to have all of these components, and necessary components can be selected arbitrarily.

[0101] There are no particular limitations on the components constituting the thin-film solar cell and the manufacturing method thereof, and any known technology can be used. For example, the technology described in known documents such as WO 2013 / 171517, WO 2013 / 180230, or JP 2012-191194 A can be used.

[0102] There is no limitation on the use of the solar cell according to the present invention, particularly the above-mentioned thin-film solar cell 14, and it can be used for any use. For example, the solar cell according to one embodiment can be used as a solar cell for building materials, a solar cell for automobiles, a solar cell for interior decoration, a solar cell for railways, a solar cell for ships, a solar cell for airplanes, a solar cell for spacecraft, a solar cell for home appliances, a solar cell for mobile phones, or a solar cell for toys.

[0103] The solar cell according to the present invention, particularly the above-mentioned thin-film solar cell 14, may be used as it is, or may be used as a component of a solar cell module. For example, as shown in FIG. 5, a solar cell module 13 having the solar cell according to the present embodiment, particularly the above-mentioned thin-film solar cell 14, on a substrate 12 is produced, and the solar cell module 13 is installed at a place of use and used. Well-known techniques can be used for the substrate 12, and for example, materials described in International Publication No. 2013 / 171517, International Publication No. 2013 / 180230, or JP-A-2012-191194 can be used as the material for the substrate 12. For example, when a building material board is used as the substrate 12, a thin-film solar cell 14 is provided on the surface of the board, and a solar cell panel for the exterior wall of a building can be produced as the solar cell module 13. EXAMPLES

[0104] Hereinafter, the present invention will be described in detail with reference to examples. However, the present invention is not limited to the following examples as long as the gist of the present invention is not exceeded.

[0105] [Preparation of coating solution] (Preparation of Coating Solution for Electron Extraction Layer) A 7.5% aqueous dispersion of tin oxide was prepared by adding ultrapure water to a 15% aqueous dispersion of tin oxide (IV) (manufactured by Alfa Aesar).

[0106] (Preparation of coating solution for active layer) Lead iodide (II) was weighed into a vial and introduced into the glove box. N,N-dimethylformamide was added as a solvent so that the concentration of lead iodide (II) was 1.3 mol / L, and then the mixture was heated and stirred at 100°C for 1 hour to prepare coating solution 1 for the active layer.

[0107] Next, formamidine hydroiodide (FAI), methylamine hydrobromide (MABr), and methylamine hydrochloride (MACl) were weighed out in a mass ratio of 10:1:1 into another vial and introduced into the glove box. By adding isopropyl alcohol as a solvent, active layer coating solution 2 with a total concentration of FAI, MABr, and MACl of 0.49 mol / L was prepared.

[0108] (Preparation of Coating Solution 1 for Hole Extraction Layer) 32 mg of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA, manufactured by Sigma-Aldrich) and 3.6 mg of 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB, manufactured by TCI) were weighed into a vial and introduced into a glove box. 1.6 mL of chlorobenzene was added as a solvent. Next, the resulting mixture was heated and stirred at 100°C for 1 hour to prepare hole extraction layer coating solution 1.

[0109] (Preparation of Coating Solution 2 for Hole Extraction Layer) Coating solution 2 for the hole extraction layer was prepared in the same manner as coating solution 1 for the hole extraction layer, except that 64 mg of PTAA and 3.6 mg of TPFB were weighed into a vial, orthodichlorobenzene was used as the solvent, and the resulting mixture was heated and stirred at 150°C instead of 100°C for 1 hour.

[0110] (Preparation of Coating Solution 3 for Hole Extraction Layer) Coating solution 3 for hole extraction layer was prepared in the same manner as coating solution 1 for hole extraction layer, except that the resulting mixed solution was heated and stirred at 70°C instead of 100°C for 1 hour.

[0111] (Preparation of Coating Solution 4 for Hole Extraction Layer) In a glove box, 170 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was weighed into a vial and 1 mL of acetonitrile was added to prepare a LiTFSI solution.

[0112] Next, 15 mg of PTAA was weighed out in a separate vial in a glove box, and 1 mL of toluene was added as a solvent to the vial. 15 μL of the LiTFSI solution and 7.5 μL of 4-tert-butylpyridine were added to the resulting solution, and the mixture was stirred at room temperature for 1 hour to prepare hole extraction layer coating solution 4.

[0113] [Example 1: Preparation of photoelectric conversion element 1] A glass substrate (manufactured by Geomatec Co., Ltd.) having a patterned indium tin oxide (ITO) transparent conductive film was subjected to ultrasonic cleaning using ultrapure water, drying by nitrogen blowing, and UV-ozone treatment.

[0114] Next, the coating solution for the electron extraction layer prepared as above was spin-coated on the above substrate at room temperature at a speed of 2000 rpm to form an electron extraction layer with a thickness of about 35 nm, and then the substrate was heated on a hot plate at 150° C. for 10 minutes.

[0115] Next, the substrate was introduced into a glove box, and 150 μL of active layer coating solution 1 heated to 100° C. was dropped onto the electron extraction layer and spin-coated at a speed of 2000 rpm. Next, the substrate was annealed by heating on a hot plate at 100° C. for 10 minutes to form a lead iodide layer. Next, after the substrate returned to room temperature, active layer coating solution 2 (120 μL) was spin-coated onto the lead iodide layer at a speed of 2000 rpm and heated at 150° C. for 20 minutes to form an organic-inorganic perovskite active layer (thickness 650 nm).

[0116] Next, after the substrate returned to room temperature, hole extraction layer coating solution 1 (200 μL) was spin-coated onto the active layer at a speed of 1500 rpm, and then heated on a hot plate at 90°C for 5 minutes to form a hole extraction layer (170 nm).

[0117] Next, an electrode was formed on the hole extraction layer by depositing a silver film with a thickness of about 100 nm using a patterning mask by resistance heating vacuum deposition. In this way, a photoelectric conversion element 1 with a size of 50 x 50 mm was produced. Furthermore, the glass with the central portion dug out and the glass substrate of the photoelectric conversion element 1 were bonded together with a sealant (photocurable resin) to seal the photoelectric conversion element 1.

[0118] [Example 2: Preparation of photoelectric conversion element 2] Photoelectric conversion element 2 was prepared using the same method as in Example 1, except that instead of spin-coating coating solution 1 for the hole extraction layer, coating solution 2 for the hole extraction layer was spin-coated onto the active layer at a speed of 1000 rpm.

[0119] Comparative Example 1: Preparation of photoelectric conversion element 3 Photoelectric conversion element 3 was produced in the same manner as in Example 1, except that instead of spin-coating hole extraction layer coating liquid 1, hole extraction layer coating liquid 3 was spin-coated onto the active layer.

[0120] [Reference Example 1: Preparation of photoelectric conversion element 4] Photoelectric conversion element 4 was prepared using the same method as in Example 1, except that instead of spin-coating hole extraction layer coating solution 1, hole extraction layer coating solution 4 was spin-coated onto the active layer at a speed of 3000 rpm.

[0121] [Evaluation of photoelectric conversion elements] A 4 mm square metal mask was attached to each of the photoelectric conversion elements 1 to 4 obtained in Examples 1 and 2, Comparative Example 1, and Reference Example 1, and the current-voltage characteristics between the ITO electrode and the silver electrode were measured. For the measurements, a source meter (Keithley, Model 2400) was used, and the irradiation light source was an air mass (AM) of 1.5 G and an irradiance of 100 mW / cm. 2A solar simulator of this type was used. From the measurement results, the initial conversion efficiency PCE (%) of the photoelectric conversion element not placed in the durability tester was calculated. Next, each of the photoelectric conversion elements 1 to 4 was placed in a high temperature and high humidity durability tester at a temperature of 60°C and a humidity of 90%, and after one day, it was removed and its current-voltage characteristics were measured. Next, each of the photoelectric conversion elements 1 to 4 was placed in the high temperature and high humidity durability tester, and after a long time had passed, it was removed and its current-voltage characteristics were measured (the time it was placed in the durability tester is shown in Table 1). The conversion efficiency PCE at each time point calculated based on each measurement result is shown in Table 1. In Table 1, the retention rate indicates the ratio of the PCE after the durability test to the initial PCE.

[0122] [Table 1]

[0123] As shown in Table 1, the initial conversion efficiency was not significantly different between Examples 1 and 2, Comparative Example 1, and Reference Example 1. On the other hand, looking at the results of the durability test, the conversion efficiency was significantly reduced in Comparative Example 1 and Reference Example 1, whereas the conversion efficiency was maintained at the same level as the initial conversion efficiency in Examples 1 and 2 even after the durability test. From the above results, it can be seen that the photoelectric conversion elements according to Examples 1 and 2 in which the coating solution was prepared under conditions of 100°C or 150°C have high durability. Thus, it is understood that although the materials used to form the buffer layer in Comparative Example 1 and Examples 1 and 2 are the same, there is a difference in their structures. Although the reason for this has not been necessarily determined at present, the present inventors speculate that the high durability is due to the smooth oxidation of the organic semiconductor compound (PTAA in this example) by preparing the coating solution for the hole extraction layer at a high temperature.

[0124] In addition, in order to support the above speculation, the inventors of the present application measured the absorbance spectrum of the coating solution for hole extraction layer according to Example 2. When the mixed solution containing PTAA and TPFB was heated and stirred at 150° C. for 10 minutes and then the absorbance spectrum was measured, a clear absorption peak was observed at 521 nm. Since PTAA does not have this absorption peak, this absorption peak at 521 nm is considered to be characteristic of oxidized PTAA. Furthermore, the magnitude of this absorption peak hardly increased even after heating and stirring for 1.5 hours. Thus, in the coating solution for hole extraction layer according to Example 2, the oxidation reaction by TPFB is considered to have progressed almost completely. On the other hand, when the mixed solution containing PTAA and TPFB was heated and stirred for 10 minutes at a lower temperature, the absorption peak at 521 nm tended not to increase very much.

[0125] From these results, the inventors of the present application presume that when the temperature is low, the oxidation reaction of the organic semiconductor compound tends to proceed very slowly, and the organic semiconductor compound is easily rendered unconductive due to its unstable oxidized state, whereas by preparing the semiconductor layer-forming coating liquid under conditions of 85°C or higher, the oxidation reaction of the organic semiconductor compound proceeds to a certain extent, resulting in a stably oxidized organic semiconductor compound, which leads to high durability of the semiconductor layer or electronic device. [Explanation of symbols]

[0126] 1 Weatherproof protective film 2. UV protection film 3,9 Gas barrier film 4,8 Getter material film 5,7 Encapsulating materials 6. Solar Cell Elements 10 Backsheet 12 Base material 13. Solar Cell Module 14 Thin-film solar cells 100 Photoelectric conversion element 101 Lower electrode 102 Buffer Layer 103 Active layer 105 Buffer Layer 107 Upper electrode 108 Base material

Claims

1. A method for manufacturing an electronic device including a semiconductor layer, comprising the steps of: the step of heating a coating liquid containing an organic semiconductor compound and a dopant for the organic semiconductor compound, which is a hypervalent iodine compound, to 85° C. or higher, and then coating the coating liquid to form the semiconductor layer having a carrier mobility of 1.0×10 −4 cm 2 / V·s or higher; The organic semiconductor compound is a triarylamine polymer in which a repeating unit contains a triarylamine structure, the dopant is a diaryliodonium salt; The aryl groups of the diaryliodonium salt each independently have a substituent. an aryl group having 30 or less carbon atoms which may be the electronic device is a solar cell element including a pair of electrodes composed of a lower electrode and an upper electrode, an active layer containing a perovskite compound between the pair of electrodes, and a buffer layer between the pair of electrodes and the active layer; The semiconductor layer is the buffer layer. A manufacturing method comprising:

2. The method according to claim 1 , wherein the buffer layer is a hole extraction layer.

3. The method according to claim 1 , wherein the buffer layer is located between the upper electrode and the active layer.

Citation Information

Patent Citations

  • Manufacturing method of charge-transport material compound, charge-transport material compound, charge-transporting thin film, manufacturing method of charge-transporting thin film, and organic electroluminescence element

    JP2007311262A

  • Composition for charge transportation film, organic electroluminescent element, organic el display, and organic el illumination

    JP2010225653A

  • Doped conjugated polymers, devices, and methods for fabricating devices

    JP2011516695A